SPIRIT 2013 Statement: defining standard protocol items for clinical trials - An-Wen Chan; Jennifer M. Tetzlaff; Douglas G. Altman; Andreas Laupacis; Peter C. Gøtzsche; Karmela Krleža-Jerić; Asbjørn Hrobjartsson; Howard Mann; Kay Dickersin; Jesse A. Berlin; Caroline J. Dore; Wendy R. Parulekar; et al.
The protocol of a clinical trial serves as the foundation for study planning, conduct, reporting, and appraisal. However, trial protocols and existing protocol guidelines vary greatly in content and quality. This article describes the systematic development and scope of SPIRIT (Standard Protocol Items: Recommendations for Interventional Trials) 2013, a guideline for the minimum content of a clinical trial protocol. The 33-item SPIRIT checklist applies to protocols for all clinical trials and focuses on content rather than format. The checklist recommends a full description of what is planned; it does not prescribe how to design or conduct a trial. By providing guidance for key content, the SPIRIT recommendations aim to facilitate the drafting of high-quality protocols. Adherence to SPIRIT would also enhance the transparency and completeness of trial protocols for the benefit of investigators, trial participants, patients, sponsors, funders, research ethics committees or institutional review boards, peer reviewers, journals, trial registries, policymakers, regulators, and other key stakeholders.